TOURISM IN FUNCTION OF DEVELOPMENT OF THE REPUBLIC OF SERBIA – Tourism and Rural Development - Marija Lakićević (Mенаџмент у хотелијерству и туризму, 2020)
Conclusions of the 5th International Scientific Conference held at the Faculty of Hotel Management and Tourism in Vrnjačka Banja on September 4th, 2020